Blue Carbon Soil Stock Development and Estimates Within Northern Florida Wetlands - Vaughn, Derrick R.; Bianchi, Thomas S.; Shields, Michael R.; Kenney, William F.; Osborne, Todd Z. (Frontiers in Earth Science, 2021)
Blue carbon habitats, such as mangroves and salt marshes, have been recognized as carbon burial hotspots; however, methods on measuring blue carbon stocks have varied and thus leave uncertainty in global blue carbon stock estimates. This study analyzes blue carbon stocks in northern Florida wetlands along the Atlantic and Gulf coasts. Carbon measurements within 1-3 meter length vibracores yield total core stocks of 9.9 – 21.5 kg C m-2 and 7.7 – 10.9 kg C m-2 for the Atlantic and Gulf coast cores, respectively. Following recent IPCC guidelines, blue carbon stock estimates in the top meter are 7.0 kg C m-2 – 8.0 kg C m-2 and 6.1 kg C m-2 - 8.6 kg C m-2 for the Atlantic and Gulf cores, respectively. Changes in stable isotopic (δ13C, C/N) and lignin biomarker (C/V) indices suggest both coastlines experienced salt marsh and mangrove transgressions into non-blue carbon habitats during the mid- to late-Holocene following relative sea-level rise. These transgressions impact carbon storage within the cores as the presence of carbon-poor soils, characteristic of non-blue carbon habitats, result in lower 1-m carbon stocks in north Florida Gulf wetlands, and a deeper extent of carbon-rich soils, characteristic of blue carbon habitats, drive higher 1-m and total carbon stocks in north Florida Atlantic wetlands. Future blue carbon research should assess carbon stocks down to bedrock when possible, as land-cover and/or climate change can impact different depths across localities. Ignoring carbon-rich soil below the top meter of soil may underestimate potential carbon emissions based on these changes.